2019
DOI: 10.1093/mnras/stz2816
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy Zoo: probabilistic morphology through Bayesian CNNs and active learning

Abstract: We use Bayesian convolutional neural networks and a novel generative model of Galaxy Zoo volunteer responses to infer posteriors for the visual morphology of galaxies. Bayesian CNN can learn from galaxy images with uncertain labels and then, for previously unlabelled galaxies, predict the probability of each possible label. Our posteriors are well-calibrated (e.g. for predicting bars, we achieve coverage errors of 10.6% within 5 responses and 2.9% within 10 responses) and hence are reliable for practical use. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 85 publications
3
98
0
Order By: Relevance
“…While ML methods such as ANN have been used for almost 30 years [226], more recent works focus on CNNs, due to their ability to process and analyze images in a relatively computationally efficient way. CNNs have been used to understand the morphology of galaxies [227][228][229], predict photometric redshifts [230,231], detect galaxy clusters [232], identify gravitational lenses [233][234][235][236] and reconstruction of images [237] Video classification is yet another field that keeps improving along with advances in ML. Karpathy et al [238] have used CNNs to classify sports-related videos found on YouTube into their corresponding sports.…”
Section: Machine Learning In Data-mining and Processingmentioning
confidence: 99%
“…While ML methods such as ANN have been used for almost 30 years [226], more recent works focus on CNNs, due to their ability to process and analyze images in a relatively computationally efficient way. CNNs have been used to understand the morphology of galaxies [227][228][229], predict photometric redshifts [230,231], detect galaxy clusters [232], identify gravitational lenses [233][234][235][236] and reconstruction of images [237] Video classification is yet another field that keeps improving along with advances in ML. Karpathy et al [238] have used CNNs to classify sports-related videos found on YouTube into their corresponding sports.…”
Section: Machine Learning In Data-mining and Processingmentioning
confidence: 99%
“…Gal (2016) first proposed the idea of approximating distributions over parameters learned in neural networks in this way and has since been used in astronomy (e.g. for the probabilistic labelling of galaxy morphologies, Walmsley et al 2019).…”
Section: Monte Carlo Dropoutmentioning
confidence: 99%
“…For a comprehensive derivation of Equations 6 and 7, as well as the implications for using an arbitrary dropout probability, we refer the reader to Walmsley et al (2019). Examples of the posterior distributions, p(k|w,D), over learned parameters using MC dropout for a randomly selected synthesised galaxy are described further in §3.1.1.…”
Section: Monte Carlo Dropoutmentioning
confidence: 99%
“…Identifying such objects is the goal of active learning algorithms which have proven to be successful in a series of astronomical applications (Solorio et al 2005;Richards et al 2012;Ishida et al 2019b). Furthermore, Bayesian neural networks (BNNs) have been shown to provide meaningful classification uncertainties that are linked to the representativeness of training sets and can be used as information for the AL loop (Möller & de Boissière 2019;Walmsley et al 2020).…”
Section: Classifier and Anomaly Detection Modulesmentioning
confidence: 99%